The Implementation of Pancasila Values by Nursing Students of Muhammadiyah University of Kudus as an Effort to Adhere to the Ethics Code of High-Quality Medical Professionals - Anwari; Fathimah Isnina; Eka Kurniawati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This study aims to enable nursing students to understand the values contained in Pancasila and to implement them in their daily lives, particularly in the professional field. By adhering to the nursing code of ethics, students are expected to develop not only technical competence but also a strong moral foundation rooted in Indonesia’s national ideology. The method applies a qualitative approach through library research. The data was collected through various academic sources, particularly from platforms such as journals and books. The results show that nursing students have implemented the values of Pancasila and the professional code of the principles embodied in Pancasila as follows: 1) Respect for Religion: Nurses must respect patients' religious beliefs, assist them in worship, especially when limited by illness, and understand that their responsibility is ultimately to God; 2) Humanity and Compassion: Nurses should act with empathy and professionalism, prioritize patient welfare, maintain confidentiality, communicate respectfully, and treat all patients equally without discrimination; 3) Unity and Teamwork: Nurses are expected to collaborate harmoniously with other healthcare professionals, prioritize patient safety over personal interest, and uphold national pride through dedicated service; 4) Deliberation and Respect: Nurses must involve patients and families in decision-making, respect their choices, communicate honestly, and avoid discussing patient matters with unauthorized individuals; 5) Justice and Equality: Nurses must provide fair and equal care to all patients, balance rights and responsibilities, avoid personal gain from healthcare facilities, and commit to continuous self-improvement.